ISSE 2008 Securing Electronic Business Processes Highlights of the Information Security Solutions Europe 2008 Conference - Pohlmann, Norbert.; Reimer, Helmut.; Schneider, Wolfgang. (Vieweg+Teubner, 2009)
This book presents the most interesting talks given at ISSE 2008 the forum for the interdisciplinary discussion of how to adequately secure electronic business processes. The topics include: - Identity Management, Information Security Management - PKI-Solutions, Economics of IT-Security - Smart Tokens, e-ID-Cards, Infrastructur Solutions - Critical Information Infrastructure Protection, Data Protection, Legal Aspects Adequate information security is one of the basic requirements of all electronic business processes. It is crucial for effective solutions that the possibilities offered by security technology can be integrated with the commercial requirements of the applications. The reader may expect state-of-the-art: best papers of the Conference ISSE 2008.